Improving the Tensile Properties of Conveyor Chains in a Tobacco Cutting Machine - ديب يوسف; علي هترة; نيرودا بركات (Latakia University Journal -Engineering Sciences Series, 2023)
This research aims to improve the tensile properties of the metal link plates used in the conveyor chains of the Hauni tobacco cutting machine in the Tobacco Directorate in Lattakia, in order to reduce the time of breakdowns and maintenance and the resulting costs, and thus improve its service life and reach a good and safe long-term conveyor belt system that meets working conditions required. In our research, the breakdown of the links of the copper metal conveyor chains was analyzed by studying their behavior while working under the influence of the load, and investigating the reasons for their collapse. With the increase in loading cycles, as a result of exposure to periodic forces of variable tension and pressure, causing the emergence of the phenomenon of fatigue, and thus the collapse of conveyor chains and very large losses in tobacco material and expensive copper connections and a decrease in productivity. The chemical analysis was carried out on the Foundry-Master device to find out the percentages of the elements included in the composition of the used copper alloy Cu -7.85 Ni -24.8 Zn -1.08 Al. Tensile test samples were prepared from the mentioned alloy according to the E8 standard, and the necessary mechanical tests were performed to find out the tensile strength on the “UNIVERSAL TESTING MACHINE” model “IBMU4-1000” because of its extensive experimental relationships with other mechanical properties. The effect of alloying elements on the tensile properties of heat treatable copper alloys was studied and the copper alloy Cu -11.81 Ni -20 Zn -2 Al was selected and the appropriate thermal, mechanical and thermal treatment was applied to it in order to improve its tensile properties. The study was conducted analytically and experimentally, and the results of the tests showed, by comparing the results, an improvement in the tensile strength when using the copper alloy Cu -11.81 Ni -20 Zn -2 Al and the appropriate thermal and mechanical treatments